2014
DOI: 10.1159/000366449
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Determinants of Sclerostin Plasma Concentration in Hemodialysis Patients

Abstract: Background: Sclerostin is a potent inhibitor of bone formation, but the meaning of its serum levels remains undetermined. We evaluated the association between sclerostin levels and clinical or biological data in hemodialyzed patients (HD), notably parathormone (PTH), biomarkers of bone turnover, vascular calcifications and mortality after 2 years. Methods: 164 HD patients were included in this observational study. The calcification score was assessed with the Kauppila method. Patients were followed for 2 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 46 publications
6
42
0
1
Order By: Relevance
“…Recently, Drechsler et al [12] reported an association between high serum sclerostin levels and better survival rate in HD patients. The same association has been reported by Viaene et al [13], but not confirmed by Delanaye et al [43]. Using the same sclerostin assay as Drechsler et al [12], Viaene et al [13] and Delanaye et al [43], we confirmed the apparent protective effect of high serum sclerostin levels with better outcome in our studied population.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Drechsler et al [12] reported an association between high serum sclerostin levels and better survival rate in HD patients. The same association has been reported by Viaene et al [13], but not confirmed by Delanaye et al [43]. Using the same sclerostin assay as Drechsler et al [12], Viaene et al [13] and Delanaye et al [43], we confirmed the apparent protective effect of high serum sclerostin levels with better outcome in our studied population.…”
Section: Discussionsupporting
confidence: 92%
“…61 Some studies show no association between sclerostin and mortality. 62 The decrease in GFR and concomitant reduction of sclerostin biodegradation is potentially the main cause of the increased concentrations of this protein in circulation, despite increases in the fraction excreted into urine with the progression of CKD. 63,64 As with subjects having normal renal function, higher concentrations of sclerostin occurs in men, which can be explained by a higher bone mass and indirectly a greater number of osteocytes.…”
Section: Sclerostin In Chronic Kidney Diseasementioning
confidence: 99%
“…67 Delanaye et al confirmed the presence of higher concentrations of sclerostin in hemodialyzed patients (HD), a positive association with age and a negative association with PTH. 62 Logically, the accumulation of sclerostin in circulation should lead to a stronger inhibition of osteoblasts and lower level of bone formation. However, lower bone turnover and increased bone resorption was observed.…”
Section: Sclerostin In Chronic Kidney Diseasementioning
confidence: 99%
“…However, the relationship between sclerostin and vascular calcification is controversial when considering ESRD patients. Delanaye et al found no association between sclerostin and the aortic calcification grade in HD patients [34], whereas Pelletier el al. reported that sclerostin levels correlated with aortic calcification severity [35].…”
Section: Discussionmentioning
confidence: 94%